ECO Smart Result Checker - Foo, Fong Yeng; Chong, Peng Hwa; Ng, Set Foong (2020)
We created a mobile app that can manage the result of students effectively in a paperless environment. This product is a green product that programmed online to assist the students and educators in result management. This mobile app makes the result checking task become more systematic and easier via integrated technology and promotes a paperless and ECO-friendly education industry. The traditional way of displaying the students’ result is a printed paper containing assessment results of all students. Assessment results are something private and confidential. Most often, the student may feel awkward if his or her result is shown publicly. The printed paper is usually displayed on the notice board outside of the lecturer's office. Students need to present personally at the lecturer’s office to check the result. Most of the time, although lecturers would hide the students’ name on the name list and replace with student identification number when the results are posted, students are still able to see and get to know each other’s results. The private and confidential of the students’ result are not protected. To secure the students’ results privately and confidentially, a mobile app was invented to enable the students to assess their individual assessment results online at anytime and anywhere. It is energy and time saving, students can check their results through this mobile app without present physically to the lecturer’s office.